2018
DOI: 10.1080/20009666.2018.1510711
|View full text |Cite
|
Sign up to set email alerts
|

Fatal intoxication with N-ethylpentylone: a case report

Abstract: Synthetic cathinones represent the latest genre of new drugs of abuse, which are increasing in popularity in part because they are readily available and because they are not detected by routine drug testing. They provide a cheaper substitute to stimulants such as methamphetamine and cocaine and are sold on the internet and in retail establishments as ‘bath salts,’ ‘plant food,’ or ‘research chemicals.’ We report a case involving a 21-year-old male who suffered arrest-related death due to intoxication with N-et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In the cases reported here, SCs were detected and quantified in post-mortem biological samples (n = 8), except for two cases. In the first of these, tests for SC metabolites and for 25INBOMe (5-HTA2 receptor agonist) were negative at hospital admission, while post-mortem GC and MS analyses revealed N-ethylpentylone in the urine [ 110 ]; in the second case, routine drug screening was performed post-mortem showing N-Ethylpentylone [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the cases reported here, SCs were detected and quantified in post-mortem biological samples (n = 8), except for two cases. In the first of these, tests for SC metabolites and for 25INBOMe (5-HTA2 receptor agonist) were negative at hospital admission, while post-mortem GC and MS analyses revealed N-ethylpentylone in the urine [ 110 ]; in the second case, routine drug screening was performed post-mortem showing N-Ethylpentylone [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…in fatal intoxication cases [ng/mL or g] Conc. in non-fatal intoxication cases [ng/mL] Reported intoxication symptoms N- Ethylhexedrone 2-(Ethylamino)-1-phenylhexan-1-one 50–60 Blood: 4–285 Urine: 147–1477 Bile: 34 Lung Brain: 5 [ 97 , 127 , 129 – 133 ] Blood: 1–84 Urine: 165 [ 100 , 127 , 134 – 136 ] Euphoria, stimulation, hyperthermia, tachycardia, vasoconstriction, aggression, dilatated pupils, anxiety, hallucinations, paranoia, acute kidney failure, insomnia, convulsions Ephylone 1-(1,3-Benzodioxol-5-yl)-2-(ethylamino)-pentan-1-one 10–100 Blood: 1–50,000 Urine: 18,000 [ 9 , 58 62 , 133 , 143 146 ] Blood: 7–149 Urine: 2000–10,700 Oral fluid: 13–1380 [ 58 , 143 , 147 , 148 ] Euphoria, stimulation, tachycardia, hyperthermia, palpitations, delusional state, aggression, psychosis, paranoia, hallucinations, confusion, sleeplessness, cardiac arrest, dissociative effects, acidosis, mydriasis rhabdomyolysis, renal failure Eutylone 1-(1,3-Benzodioxol-5-yl)-2-(ethylamino)-butan-1-one 50–200 Blood: 1–11,000 Urine: 192,000 Gastric content: 2120 Fat tissue: 1310 [ 65 , 67 , 150 ] Blood: 1–3600 Urine: 54–18,400 [ 65 , 67 , 151 154 ] ...…”
Section: Pharmacology and Toxicitymentioning
confidence: 99%
“…Additionally, studies in zebrafish showed its neurotoxicity, cardiotoxicity and developmental toxicity [ 142 ]. There are reports of deaths with ephylone detected in biological material [ 9 , 58 62 , 133 , 143 146 ], as well as cases of non-fatal poisoning [ 58 , 143 , 147 , 148 ]. The blood concentrations of ephylone detected in these cases were 1–50,000 ng/mL and 7–149 ng/mL, respectively (Table 1 ).…”
Section: Pharmacology and Toxicitymentioning
confidence: 99%
“…Consequently, when pentylone was scheduled (DEA, 2014), new beta‐keto‐methylenedioxyamphetamines, such as N‐ethyl‐pentylone (NEP, also known as ephylone and N‐ethylnorpentylone), broke into the illicit market. In fact, some fatalities and acute intoxications after NEP consumption have been recently reported (Blanco et al, 2021; Costa et al, 2019; Ikeji et al, 2018; Krotulski et al, 2018; Thirakul et al, 2017). In 2017 and 2018, NEP was the most commonly reported synthetic cathinone, accounting for approximately 50% of identifications (Drug Enforcement Administration (DEA) 2018).…”
Section: Introductionmentioning
confidence: 99%
“…talities and acute intoxications after NEP consumption have been recently reported (Blanco et al, 2021;Costa et al, 2019;Ikeji et al, 2018;Krotulski et al, 2018;Thirakul et al, 2017). In 2017 and 2018, NEP was the most commonly reported synthetic cathinone, accounting for approximately 50% of identifications (Drug Enforcement Administration (DEA) 2018).…”
mentioning
confidence: 99%